The impact of experiencing severe physical abuse in childhood on adolescent refugees’ emotional distress and integration during the COVID-19 pandemic - Potter, Flurina; Dohrmann, Katalin; Rockstroh, Brigitte; Schauer, Maggie; Crombach, Anselm (Frontiers in Psychology, 2022)
Background. Accumulating evidence highlights the importance of pre- and post- migration stressors on refugees’ mental health and integration. In addition to migration-associated stressors, experiences earlier in life such as physical abuse in childhood as well as current life stress as produced by the Covid-19-pandemic may impair mental health and successful integration – yet evidence on these further risks is still limited. The present study explicitly focused on the impact of severe physical abuse in childhood during the Covid-19 pandemic and evaluated the impact of these additional stressors on emotional distress and integration of refugees in Germany. Methods. The sample included 80 refugees, 88.8% male, mean age 19.7 years. In a semi-structured interview, trained psychologists screened for emotional distress, using the Refugee Health Screener, and integration status, using the Integration Index. The experience of severe physical abuse in childhood was quantified as a yes/no response to the question: “Have you been hit so badly before the age of 15 that you had to go to hospital or needed medical attention?” Multiple hierarchical regression analyses further included gender, age, residence status, months since the start of the Covid-19 pandemic and length of stay in Germany to predict emotional distress and integration. Results. Two regression analyses determined significant predictors of (1) emotional distress (adjusted R² = .23): duration of being in the pandemic (ß = .38, p < .001) and severe physical abuse in childhood (ß = .31, p = .005), and significant predictors of (2) integration (adjusted R² = .50): length of stay in Germany (ß = .60, p < .001), severe physical abuse in childhood (ß = .24, p = .011) and emotional distress (ß = -.29, p = .002). Conclusion. In addition to migration-associated stressors, severe physical abuse in childhood constitutes a pre-migration risk, which crucially affects the well-being, emotional distress and integration of refugees in Germany.